Application of electrochemical advanced oxidation to bisphenol A degradation in water. Effect of sulfate and chloride ions. (March 2018) - Burgos-Castillo, Rutely C.; Sirés, Ignasi; Sillanpää, Mika; Brillas, Enric
Abstract: Electrochemical oxidation with electrogenerated H2 O2 (EO- H2 O2 ), electro-Fenton (EF), photoelectro-Fenton (PEF) and solar PEF (SPEF) have been applied to mineralize bisphenol A solutions in 0.050 M Na2 SO4 or 0.008 M NaCl + 0.047 M Na2 SO4 at pH 3.0. The assays were performed in an undivided cell with a boron-doped diamond (BDD) anode and an air-diffusion cathode for continuous H2 O2 production. The PEF and SPEF processes yielded almost total mineralization due to the potent synergistic action of generated hydroxyl radicals and active chlorine, in conjunction with the photolytic action of UV radiation. The higher intensity of UV rays from sunlight explained the superior oxidation ability of SPEF. The effect of applied current density was studied in all treatments, whereas the role of bisphenol A concentration was examined in PEF. Bisphenol A abatement followed a pseudo-first-order kinetics, which was very quick in SPEF since UV light favored a large production of hydroxyl radicals from Fenton's reaction. Eight non-chlorinated and six chlorinated aromatics were identified as primary products in the chloride matrix. Ketomalonic, tartronic, maleic and oxalic acids were detected as final short-chain aliphatic carboxylic acids. The large stability of Fe(III)-oxalate complexes in EF compared to their fast photomineralization in PEF and PEF accounted for by the superior oxidation power of the latter processes. Highlights: Mineralization of bisphenol A at pH 3.0 increases as: EO-H2 O2  < EF < PEF < SPEF. Almost total mineralization by PEF and SPEF in sulfate medium and chloride matrices. Slower degradation in chloride medium due to formation of chlorinated intermediates. Very faster decay of bisphenol A by SPEF due to high OH production induced by sunlight Identification of 8 non-chlorinated and 5 chlorinated primary aromatics and 4 carboxylic acids.